Phylogeographic history of flat periwinkles, Littorina fabalis and L. obtusata - Graciela Sotelo; Mårten Duvetorp; Diana Costa; Marina Panova; Kerstin Johannesson; Rui Faria (BMC Evolutionary Biology, 2020)
Abstract Background The flat periwinkles, Littorina fabalis and L. obtusata, are two sister species widely distributed throughout the Northern Atlantic shores with high potential to inform us about the process of ecological speciation in the intertidal. However, whether gene flow has occurred during their divergence is still a matter of debate. A comprehensive assessment of the genetic diversity of these species is also lacking and their main glacial refugia and dispersal barriers remain largely unknown. In order to fill these gaps, we sequenced two mitochondrial genes and two nuclear fragments to perform a phylogeographic analysis of flat periwinkles across their distribution range. Results We identified two main clades largely composed by species-specific haplotypes corresponding to L. obtusata and L. fabalis, with moderate to strong support, respectively. Importantly, a model of divergence with gene flow between the two species (from L. obtusata to L. fabalis) was better supported, both in Iberia and in northern-central Europe. Three mitochondrial clades were detected within L. fabalis and two within L. obtusata, with strong divergence between Iberia and the remaining populations. The largest component of the genetic variance within each species was explained by differences between geographic regions associated with these clades. Our data suggests that overall intraspecific genetic diversity is similar between the two flat periwinkle species and that populations from Iberia tend to be less diverse than populations from northern-central Europe. Conclusions The phylogeographic analysis of this sister-species pair supports divergence with gene flow. This system thus provides us with the opportunity to study the contribution of gene flow and natural selection during diversification. The distribution of the different clades suggests the existence of glacial refugia in Iberia and northern-central Europe for both species, with a main phylogeographic break between these regions. Although the genetic diversity results are not fully conclusive, the lower diversity observed in Iberia could reflect marginal conditions at the southern limit of their distribution range during the current interglacial period.